An Analytical Study of Fahmida Riaz's Novel "Godavari" - Dr. Aziza Saeed,; Dr. Khizra Tabassum,; Dr. Zeenat Afshan,; Dr. Sobia Manzoor,,; Rida Batool Naqvi,; Syed Azwar Abbas, (Al-Qanṭara, 2024)
Fahmida Riaz was born on 28 July 1946 and died on 21 November 2018. She was a Pakistani progressive writer, poet, social activist for human rights and women's rights. Among his famous works are “Godavari”, “Khat Mirmooz” and “Khana Aab-e-Gul”. “Khana Aab-e-Gul” is an Urdu translation of the famous Masnavi of the Persian language by Maulana Room. The unique author of 15 literary books has been surrounded by controversies throughout her life. When her collection “Badan Darida” came out, she was accused of using sexy and sensitive language. She has translated the books of Shah Abdul Latif Bhitai and Sheikh Ayaz from Sindhi language into Urdu. Fed up with the dictatorship of Muhammad Zia-ul-Haq, Fehmida Riaz sought refuge in India from Pakistan, where she spent many years. Her collection of poetry is his crime and describes the persecution of General Zia-ul-Haq. She has described her experience in her collections. This Article is Written about her novel“Godavari”..